2016
DOI: 10.1186/s13065-016-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of dosimetry tools for the assessment of e-cigarette aerosol and cigarette smoke generated on two different in vitro exposure systems

Abstract: The diluted aerosols from a cigarette (3R4F) and an e-cigarette (Vype ePen) were compared in two commercially available in vitro exposure systems: the Borgwaldt RM20S and Vitrocell VC10. Dosimetry was assessed by measuring deposited aerosol mass in the exposure chambers via quartz crystal microbalances, followed by quantification of deposited nicotine on their surface. The two exposure systems were shown to generate the same aerosols (pre-dilution) within analytically quantified nicotine concentration levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…In our recent e-cigarette studies, we have shown the importance of expressing dose as a function of delivered nicotine, when conducting comparative studies across different tobacco and nicotine product categories. Azzopardi et al 25 and Adamson et al 7,28 showed how deposited mass and nicotine quantification at the cellular exposure interface enable appropriate extrapolation and comparisons in an aerosol matrix. Different types of e-cigarettes and e-liquids generate different volumes of aerosol and deliver different amounts of nicotine, however typically smokers who switch from cigarette to nicotine delivery devices adapt their behavior to potentially titrate for nicotine 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In our recent e-cigarette studies, we have shown the importance of expressing dose as a function of delivered nicotine, when conducting comparative studies across different tobacco and nicotine product categories. Azzopardi et al 25 and Adamson et al 7,28 showed how deposited mass and nicotine quantification at the cellular exposure interface enable appropriate extrapolation and comparisons in an aerosol matrix. Different types of e-cigarettes and e-liquids generate different volumes of aerosol and deliver different amounts of nicotine, however typically smokers who switch from cigarette to nicotine delivery devices adapt their behavior to potentially titrate for nicotine 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, while numerous studies have analyzed the aerosol constitu-ents generated by tobacco products and NGPs, [12][13][14] the exposure dosimetry at the ALI and the consistency of in vitro puff-to-puff aerosol production have only recently been realised. [15][16][17] Reproducible aerosol generation is crucial to developing standardized dosimetry measurements. In addition, measuring appropriate markers, for example, nicotine, at the cellular/tissue target is essential to understanding subsequent biological responses.…”
Section: Introductionmentioning
confidence: 99%
“…A number of dosimetry tools can be used to support the assessment of aerosols generated using in vitro exposure systems and include particle size and number evaluation, analytical chemical quantitation of exposure constituents, and mass deposition either by gravimetric means or analytical quantification. [15][16][17][18][19] For example, Neilson et al, 20 as part of an in vitro assessment of e-cigarettes in RhuA using a VC1 Smoking Robot, employed the use of quartz crystal microbalances (QCMs) to measure deposited mass and confirm aerosol delivery to the tissues. In another example, using a VC1 smoking robot, Fields et al, 21 assessed aerosols from reference 3R4F cigarette smoke and e-cigarettes by fluorometric analysis of aerosols collected at generation source and cellular exposure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations